Pengaruh Instagram Ads, Desain Grafis Dan Promosi Penjualan Terhadap Minat Beli Konsumen Di PT. Sayur Box - Ahmad Alvin Febryansyah; Siti Asiyah; Rahmawati Rahmawati (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The purpose of this research is to describe interest in buying, instagram ads, graphic design and promotion and to know the influence of instagram ads, graphic design and promotion to interest in buying on SayurBox user. The method in this research is using quantitative method. The sample of this research is housewife in Malang City by using non probability sampling that is purposive sampling, that is counted 60 respondents. Methods in using data using questionnaires. The analysis process used in this research is the multiple regression analysis. The result of this research indicate that simultaneously instagram ads, graphic design and promotion has positive and significant effect to interest in buying on SayurBox user. While partially Instagram Ads has positive and significant effect to interest in buying,graphic design has negative and not significant effect to interest in buying and promotion has positive and significant effect to interest in buying on SayurBox user. Keywords : Interest in Buying, Instagram Ads, Graphic Design, Promotion